FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR (Students' Journal of Accounting and Banking, 2013)
This study aims to examine the effect of audit quality, audit opinion a year earlier, the company's financial condition, and the company's revenue growth going concern audit opinion on the manufacturing companies experiencing financial difficulties (financial distress). Going concern is a doubt a company's continued survival. Study sample was 65 manufacturing companies experiencing financial difficulties that are listed on the Stock Exchange 2006-2010. Sampling technique using a purposive sampling method. The analysis used in this study using Logistic Regression for the dummy variables used to test the descriptive statistics to determine the average (mean), maximum value, minimum value, standard deviation and frequency distribution test to determine the frequency, percent, valid percent, kumulative percent, and test models that include the Hosmer and Lemeshhow's Goodness of Fit Test, Log Likelihood and Naglekerke R Square. The results of this study is based on a sample of 65 companies, 9 companies receive non going-concern opinion and as many as 56 companies that received going-concern opinion. Of test data analysis showed that the positive effect of audit quality is not  ignificant to the receipt of a going concern audit opinion. Previous year's audit opinion a significant positive effect on receipt of a going concern audit opinion. Company's financial condition using the model Zmijeski positive effect on receipt of significant going-concern audit opinion. Company's inancial condition using the model of Revised Altman and Springate models models no significant negative impact on revenues going concern audit opinion. While the company's growth is significantly negative effect on revenues going concern audit opinion Keywords: Acceptance of Going Concern  dit Opinions, Quality Audit, Audit Opinion, the Company's Financial Condition, Growth Company.